Schistosome-Derived Molecules as Modulating Actors of the Immune System and Promising Candidates to Treat Autoimmune and Inflammatory Diseases - Luis Janssen; Gisele Lorranna Silva Santos; Herick Sampaio Muller; Anderson Rodrigues Araújo Vieira; Tatiana Amabile de Campos; Vicente de Paulo Martins (Journal of Immunology Research)
It is long known that some parasite infections are able to modulate specific pathways of host’s metabolism and immune responses. This modulation is not only important in order to understand the host-pathogen interactions and to develop treatments against the parasites themselves but also important in the development of treatments against autoimmune and inflammatory diseases. Throughout the life cycle of schistosomes the mammalian hosts are exposed to several biomolecules that are excreted/secreted from the parasite infective stage, named cercariae, from their tegument, present in adult and larval stages, and finally from their eggs. These molecules can induce the activation and modulation of innate and adaptive responses as well as enabling the evasion of the parasite from host defense mechanisms. Immunomodulatory effects of helminth infections and egg molecules are clear, as well as their ability to downregulate proinflammatory cytokines, upregulate anti-inflammatory cytokines, and drive a Th2 type of immune response. We believe that schistosomes can be used as a model to understand the potential applications of helminths and helminth-derived molecules against autoimmune and inflammatory diseases.